2022
DOI: 10.1029/2022gl098582
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Control on Ground Motions and Landslides From the 2015 Gorkha Earthquake

Abstract: Landslides triggered by earthquake shaking pose a significant hazard in active mountain regions. Steep topography promotes gravitational instabilities and can amplify the seismic wavefield; however, the relationship between topographic amplification and landsliding is poorly understood. Here, we use numerical methods to investigate the link between low‐frequency ground shaking, topographic amplification, and the landslide distribution from the 2015 Gorkha, Nepal earthquake. Results show that the largest landsl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The use of ground motion simulations to examine coseismic landslides are quite limited in the literature (Harp et al, 2014;Chen and Wang, 2022;Dunham et al, 2022;Feng et al, 2022;Sun and Huang, 2023). Their focus mainly gravitates around better assessment of landslide displacements by coupling their simulation results with physically-based methods or the effect of topographic amplification on landslide sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ground motion simulations to examine coseismic landslides are quite limited in the literature (Harp et al, 2014;Chen and Wang, 2022;Dunham et al, 2022;Feng et al, 2022;Sun and Huang, 2023). Their focus mainly gravitates around better assessment of landslide displacements by coupling their simulation results with physically-based methods or the effect of topographic amplification on landslide sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Using numerical simulations, several works (e.g., Bouchon, 1985;Geli et al, 1988;Tripe et al, 2013) found the high relevance of the site effects of a slope on the amplification of the ground motion. Following this, many works also saw how the 3d effects from geology and topography are relevant in landslide occurrence by studying the incoming waves (e.g., Khalil and Lopez-Caballero, 2021;He et al, 2020;Dunham et al, 2022). Because those analyses are at local scales, they implement complex constitutive models for the soil materials' resistance and rupture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that fault geometry and slip are responsible for producing the broad wavefield of earthquakes, and the details of the wave fields affect the propagation and the local scattering, attenuation, and amplification of seismic wavefields. Wave attenuation tends to occur in valleys, and amplification occurs near peaks and high up on ridges (Dunham et al., 2022), but the details of this here are unknown. Another possible influence could have been deep bedrock weathering and fracture structure, such as has been implicated in the Chamoli, Uttarakhand, India ridge failure on 7 February 2021 (Reynolds et al., 2021; Richardson & Reynolds, 2000; Shugar et al., 2021).…”
Section: Why Was the 1970 Earthquake Special?mentioning
confidence: 94%
“…Seismic body waves (p-waves and swaves) arriving obliquely toward the surface tend to attenuate near valley floors, where glacier lakes occur, helping to protect moraine dams against damage from seismic shaking. Seismic waveform modeling of the 2015 Nepal Gorkha earthquake (Dunham et al, 2022) and previous related work , Lee, Chan, et al, 2009 has highlighted the role of seismic body-wave attenuation deep in valleys, and amplification on ridges and some valley walls. Surface waves, such as Love waves and Rayleigh waves 3) for the 59 earthquakes (shown in Figure 1) and timing for the 67 GLOFs in the comprehensive Peruvian and Bolivian inventory (Emmer, Wood, et al, 2022).…”
Section: Earthquake Relationships To Glofsmentioning
confidence: 99%